2020
DOI: 10.3390/app10186195
|View full text |Cite
|
Sign up to set email alerts
|

Blast Vibration Control in A Hydropower Station for the Safety of Adjacent Structure

Abstract: The transverse cofferdam in Xiangjiaba hydropower station was a water retaining concrete structure with a length of 126 m, a width of 12 m, and a height of 25.2 m, consisting of masonry, plain concrete structure (PC), and roller compacted concrete (RCC), which had to be demolished by blasting after the dam was built. There were many precise instruments nearby the cofferdam which had strict restrictions on blasting vibration. Therefore, the cofferdam was divided into six blasting regions, including land blastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A total of 15 field monitoring experiments were conducted (as shown in Table 1), and 45 sets of shock wave pressure data from underwater drilling blasting were obtained for different source distances (8-323 m), explosive weights (6-115 kg), numbers of blastholes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and water depths (6.2-20.0 m). The field monitoring results showed that the shock wave pressure was in the range of 0.04-12.89 ×10 5 Pa.…”
Section: Field Monitoring Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 15 field monitoring experiments were conducted (as shown in Table 1), and 45 sets of shock wave pressure data from underwater drilling blasting were obtained for different source distances (8-323 m), explosive weights (6-115 kg), numbers of blastholes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and water depths (6.2-20.0 m). The field monitoring results showed that the shock wave pressure was in the range of 0.04-12.89 ×10 5 Pa.…”
Section: Field Monitoring Resultsmentioning
confidence: 99%
“…In terms of field monitoring, Tatlısuluo glu et al investigated the engineering characteristics of underwater blast shock waves in offshore waters in Turkey [7]. Ma et al obtained the attenuation pattern of underwater drilling blasting shock waves in rock masses using the underwater blast of a hydropower station as the background [8]. Ge et al provided a semi-theoretical and semi-empirical equation for underwater shock waves using shallow underwater drilling blasting tests on a seashore [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that basic seismic monitoring approaches do not involve natural vibration data from nearby objects, regardless of their effect on total vibration. For example, in [26,29] the measurements were carried out the same way, but the instruments were located at selected points without direct recording of any nearby object's natural vibration. However, additional research on the dominant frequency changes when possible resonance is considered, which may improve the accuracy of the drilling and blasting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Blast waves have different characteristics that can be extracted using Fourier transform [27], wavelet transform, and fractal analysis [28][29][30]. The wavelet wave signal decomposition is used to derive the wavelet coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…In the aspect of the propagation law of water hammer wave, Peng [11] derives the vibration frequency prediction formula considering the altitude effect. In addition, Ma et al [12] analyze the peak velocity (PPV) of surface blasting of the same structure and predict the peak velocity of underwater blasting (PPV). Besides, Huang [13] establishes the numerical model of multimaterial arbitrary Lagrangian-Eulerian (MMALE) technique and studies the peak pressure of the explosive underwater explosion.…”
Section: State Of the Artmentioning
confidence: 99%